Analysis of the Potential Development of Goats and Sheep in Batu Bara - G.A.W Siregar; A.H. Daulay; A. Purba; Harahap, T.M.N.H (Talenta Publisher, 2022)
One of the districts that have the potential to develop goats and sheep in North Sumatra is Batu Bara Regency. For this reason, a study was conducted to determine the potential of livestock resources, the area and capacity of goats and sheep, and alternative strategies that are effective in developing goats and sheep in Batu Bara Regency. This research was conducted in September – November 2021 using the stratified sampling research method in the sub-districts in Batu Bara Regency and the purposive sampling method, which resulted in the highest population sub-district, namely Laut Tador District, the medium population in Air Putih District, and the low population being Sei Suka District. . Sampling using the method of determining the quota of 30 respondents in each sub-district. The respondents were interviewed to obtain information regarding goat and sheep livestock. Data analysis carried out is descriptive analysis, location quotient, livestock density, feed concentration index, carrying capacity of agricultural and plantation waste, carrying capacity index of agricultural and plantation waste, capacity to increase the population of ruminant livestock (KPPTR), and SWOT analysis. Based on the research results, Batu Bara Regency has the potential to develop goats and sheep. Five areas each become the basis for goats and sheep in the district. The carrying capacity of goats and sheep in Batu Bara Regency is 168,040.04 ST for goats and 166,236.56 ST for sheep. The right strategy and priority is the SO strategy.